High reduction of interfacial charge recombination in colloidal quantum dot solar cells by metal oxide surface passivation1. Issue 12 (28th March 2015) - Chang, Jin; Kuga, Yuki; Mora-Seró, Iván; Toyoda, Taro; Ogomi, Yuhei; Hayase, Shuzi; Bisquert, Juan; Shen, Qing
<x xml:space="preserve">Abstract</x> High efficiency PbS quantum dot solar cells have been achieved by utilizing a nanowire architecture and proper surface passivation strategy.